Perancangan Ulang Mesin Spot Welding Menggunakan Metode Benchmarking (Studi Kasus: Bengkel Fabrikasi Logam Dan Manufaktur SMK Negeri 2 Surakarta) - Ismail Hakim Asy Syidiq; Febrina Agusti; Ringgo Ismoyo Buwono (Politeknik Kampar, 2025)
Spot welding is used as a tool to meet the UKK (Skill Competency Test) requirements in the Metal Fabrication and Manufacturing Engineering department at SMK Negeri 2 Surakarta in the form of welding workpieces from iron plates. The results of the welding are non-sticky and perforated iron plates. This research aims to redesign the spot welding machine by adding a TDR (Time Delay Relay) component to regulate the welding time using the benchmarking method. Data collection through interviews and observation. The results of the benchmarking analysis show that spot welding has easier welding specifications, has TDR and automatic switch components, dimensions of 45 x 23 x 15 cm and is capable of welding up to a plate thickness of 1,5 + 1,5 mm. Has a selling price of Rp. 1,200,000,-, so that it is able to compete in the market.